Finding home again - Jackson, Brenda (Brenda Streater) (Jackson, Brenda (Brenda Streater). Catalina Cove., 2019)
"Bryce Witherspoon's heart races every time she sees Kaegan Chambray. Everyone in town knows they can't stand each other, but the truth is, even though the man broke her heart ten years ago, she still feels that irresistible, oh-so-familiar jolt of desire. When Kaegan returned to Catalina Cove to run the family business, he knew there'd be no avoiding Bryce. The woman he thought he'd one day marry was instead the biggest heartbreak of his life. But when Bryce lets slip a devastating secret, he discovers just how wrong he was to let her go all those years ago. He knows they both still feel the spark between them, but it'll take more than attraction to convince her. Kaegan will pull out all the stops to show Bryce he's the man who can give her the future they once dreamed of--if only they give love a second chance." -- Amazon.